2007
DOI: 10.1126/science.1142842
|View full text |Cite
|
Sign up to set email alerts
|

A Common Variant on Chromosome 9p21 Affects the Risk of Myocardial Infarction

Abstract: The global endemic of cardiovascular diseases calls for improved risk assessment and treatment. Here, we describe an association between myocardial infarction (MI) and a common sequence variant on chromosome 9p21. This study included a total of 4587 cases and 12,767 controls. The identified variant, adjacent to the tumor suppressor genes CDKN2A and CDKN2B, was associated with the disease with high significance. Approximately 21% of individuals in the population are homozygous for this variant, and their estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
624
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,434 publications
(651 citation statements)
references
References 8 publications
22
624
3
2
Order By: Relevance
“…The association for the GRS and higher odds of MI was consistent with previous literature analyzing SNPs in the chromosome 9p21 and higher risk of CHD and mortality 6, 10, 12. Moreover, we observed that participants with the highest genetic risk in combination with the highest lifestyle risk factors (both all‐together as well as individually) had higher odds of MI.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The association for the GRS and higher odds of MI was consistent with previous literature analyzing SNPs in the chromosome 9p21 and higher risk of CHD and mortality 6, 10, 12. Moreover, we observed that participants with the highest genetic risk in combination with the highest lifestyle risk factors (both all‐together as well as individually) had higher odds of MI.…”
Section: Discussionsupporting
confidence: 92%
“…Although the genetic variants used in the GRS have been associated with increased risk of CHD in European populations,6, 10, 12 they account for a modest portion of the variability in MI, and other genetic variants (for example, in genes of the inflammation response) could have a stronger effect in this population. A more comprehensive evaluation of gene–environment interactions with genetic markers in additional loci warrants future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations